(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept of linguistic personality is multifaceted, and today it is studied by the field of linguopersonology in linguistics. Each language owner, as a separate person, shows the possibilities of using the language in his own way. A literary text can express the linguistic identity of representatives of different nationalities. A literary text can express the linguistic identity of representatives of different nationalities. There are specific aspects of expressing the linguistic identity of characters of different nationalities, which are discussed in the article.